l‐α‐Lysophosphatidylinositol (LPI) aggravates myocardial ischemia/reperfusion injury via a GPR55/ROCK‐dependent pathway - Robertson‐Gray, Olivia J. (Pharmacol Res Perspect, 2019)
The phospholipid l‐α‐lysophosphatidylinositol (LPI), an endogenous ligand for GPR55, is elevated in patients with acute coronary syndrome, and a GPR55 antagonist cannabidiol (CBD) reduces experimental ischemia/reperfusion (I/R) injury. While LPI activates multiple signaling pathways, little is known about which ones are important in cardiomyocytes. In this study we explored whether activation of the Rho kinase/ROCK/p38 MAPK pathway is responsible for LPI‐induced extension of I/R injury. Using a high‐throughput screening method (dynamic mass redistribution; DMR), mouse‐ and human‐induced pluripotent stem cell (iPSC) cardiomyocytes exposed to LPI were shown to exhibit a rapid, sustained, and concentration‐dependent (1 nmol L(−1)‐30 μmol L(−1)) cellular response. Y‐27632 (ROCK inhibitor; 10 & 50 μmol L(−1)) and CBD (1 μmol L(−1)) both abolished the DMR response to LPI (10 μmol L(−1)). In murine iPSC cardiomyocytes, LPI‐induced ROCK and p38 MAPK phosphorylation, both of which were prevented by Y‐27632 and CBD, but did not induce JNK activation or cleavage of caspase‐3. In hearts isolated from wild type (WT) mice subjected to 30 minutes global I/R, LPI (10 μmol L(−1)) administered via the coronary circulation increased infarct size when applied prior to ischemia onset, but not when given at the time of reperfusion. The exacerbation of tissue injury by LPI was not seen in hearts from GPR55(−/−) mice or in the presence of Y‐27632, confirming that injury is mediated via the GPR55/ROCK/p38 MAPK pathway. These findings suggest that raised levels of LPI in the vicinity of a developing infarct may worsen the outcome of AMI.